TRITON: A Multi-GPU open source 2D hydrodynamic flood model. (July 2021) - Morales-Hernández, M.; Sharif, Md B.; Kalyanapu, A.; Ghafoor, S.K.; Dullo, T.T.; Gangrade, S.; Kao, S.-C.; Norman, M.R.; Evans, K.J.
Abstract: A new open source multi-GPU 2D flood model called TRITON is presented in this work. The model solves the 2D shallow water equations with source terms using a time-explicit first order upwind scheme based on an Augmented Roe's solver that incorporates a careful estimation of bed strengths and a local implicit formulation of friction terms. The scheme is demonstrated to be first order accurate, robust and able to solve for flows under various conditions. TRITON is implemented such that the model effectively utilizes heterogeneous architectures, from single to multiple CPUs and GPUs. Different test cases are shown to illustrate the capabilities and performance of the model, showing promising runtimes for large spatial and temporal scales when leveraging the computer power of GPUs. Under this hardware configuration, communication and input/output subroutines may impact the scalability. The code is developed under an open source license and can be freely downloaded in https://code.ornl.gov/hydro/triton . Highlights: TRITON is released as a multi-GPU open source 2D hydrodynamic flood code. It solves the 2D shallow water equations using a first order time-explicit scheme. It runs efficiently for realistic configurations using heterogeneous architectures. The runoff capability is demonstrated to be convenient for flood modeling. Communication and I/O times may represent a bottleneck for operational purposes.